Solar-thermal conversion and steam generation: a review - Shi, Lei; Wang, Xinzhi; Hu, Yanwei; He, Yurong; Yan, Yuying (Elsevier, 2020)
Recently, steam generation systems based on solar-thermal conversion have received much interest, and this may be due to the widespread use of solar energy and water sources such as oceans and lakes. The photo-thermal desalination system becomes attractive as it can convert absorbed solar light energy into thermal energy and realise the desalination and water purification of saline water through the evaporation process. In this paper, the research status of solar-thermal conversion materials such as metal-based materials, semiconductor materials, carbon-base materials, organic polymer materials, composite photo-thermal materials and their solar-thermal conversion mechanism in recent years are reviewed. The physical process and evaluation principle of solar-thermal conversion are both carefully introduced. The methods of optimising thermal management and increasing the evaporation rate of a hybrid system are also introduced in detail. Four main applications of solar-thermal conversion technologies (seawater desalination, wastewater purification, sterilisation and power generation) are discussed. Finally, based on the above analysis, the prospects and challenges for future research in the field of desalination are discussed from an engineering and scientific viewpoint to promote the direction of research, in order to stimulate future development and accelerate commercial application.